Thiết kế hoạt động trải nghiệm trong dạy học nhằm phát triển năng lực giao tiếp và hợp tác cho học sinh tiểu học - Nguyễn Thị Hòa, Nguyễn Thị Hòa; Vũ Lệ Hoa, Vũ Lệ Hoa (Tạp chí Giáo dục, 2026)
Communication and collaboration are two core competencies emphasized in the 2018 General Education Curriculum of Vietnam, playing a significant role in shaping students’ key competencies and personal development at the primary level. However, teaching practice reveals that fostering these skills remains challenging due to the lack of concrete activity models. This article employs a literature review method to clarify the concepts of communication and collaboration competencies, as well as the role of experiential learning in primary education. Based on theoretical foundations, the author analyzes the behavioral indicators of these competencies through experiential activities and proposes a systematic process for designing such activities in subject teaching. Finally, the study illustrates the application of this process through a specific example, thereby initially demonstrating the feasibility and pedagogical significance of integrating competency development into primary education.